Development of a NiMn2O4@Fe3O4 nanocomposite-based dispersive solid phase extraction for the accurate and sensitive determination of lead in mint tea samples prior to flame atomic absorption spectrometer measurement - Zeytinci, Nagehan Kubra; Zaman, Buse Tugba; Bozyigit, Gamze Dalgic; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
In this study, NiMn2O4@Fe3O4 nanocomposite was synthesized and utilized as an adsorbent for the preconcentration/extraction of lead prior to its determination by flame atomic absorption spectrometry. Comprehensive optimization studies were carried out univariately to enhance the extraction and recovery efficiency of the lead ions. The developed dispersive solid phase extraction method sought to minimize the use of extraction solvents. In this study, the limit of detection was presented as 15 mu g/kg and LDR was between 30 - 964 mu g/kg. The relative standard deviation (%RSD) values were found to be within the range of 8.3-12.12. The recovery experiments were performed in mint tea samples, and the percent recovery values were calculated within the range of 91.7 - 108 and 65.8 - 111 for the matrix-matched calibration strategy and external calibration, respectively. Precise and accurate determination of lead ions was achieved by applying the developed NiMn2O4@Fe3O4 nanocomposite-based dSPE-FAAS method.
Keywords: Lead; Preconcentration; Mint tea; Flame atomic absorption spectrometry; HIGH-PERFORMANCE; HEAVY-METALS; WATER; ELECTRODE; 1-(2-PYRIDYLAZO)-2-NAPHTHOL; NANOPARTICLES; ADSORPTION; Chemistry; Food Science & Technology